Studi Fenomenologis Resiliensi dan Karakter Survive Peserta Didik di Sekolah Bantaran Sungai Kota Banjarmasin - Selamat Maulana; Sarbaini; Nisa, Uswatun Nisa (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study aims to understand the phenomenon of resilience and survival character of students in schools located along the riverbanks of Banjarmasin City. The unique geographical characteristics and diverse environmental challenges, including flood risks and limited access, have drawn authors' attention to explore students’ direct experiences in facing these obstacles and factors that support their persistence and achievements. Data were collected through in-depth interviews, participatory observations, and document analysis, involving students, teachers, and parents as key informants. The findings reveal that students’ resilience is formed through social support from families and communities, adaptation to the environment, and internalisation of local values such as cooperation and perseverance. Students' survival character is evident in their ability to overcome physical limitations, such as long journeys using wooden boats (jukung) to go to school, and psychological challenges, such as social stigma associated with their living environment. Additionally, the role of teachers as motivators and facilitators of creative learning is key to fostering students' optimism. This study highlights the importance of a holistic approach to support education in marginalized areas. Its practical implications include the development of locally-based inclusive education policies, teacher training to enhance competencies in unique environments, and the improvement of school infrastructure along riverbanks. This study contributes to the literature on educational resilience, particularly in regions with geographical and social challenges, while also serving as an inspiration for educational development in similar areas.